2017
DOI: 10.1101/202424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Across-subjects classification of stimulus modality from human MEG high frequency activity

Abstract: Single-trial analyses have the potential to uncover meaningful brain dynamics that are obscured when averaging across trials. However, low signal-to-noise ratio (SNR) can impede the use of single-trial analyses and decoding methods. In this study, we investigate the applicability of a single-trial approach to decode stimulus modality from magnetoencephalography (MEG) high frequency activity. In order to classify the auditory versus visual presentation of words, we combine beamformer source reconstruction with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…A substantial improvement in the performance of new strategy was observed compared with traditional ones. The predictive performance of one study on the SZ outcome of another was reported to be a key criterion for evaluating the reproducibility of the signatures identified by different datasets . The predictive performance (both ACCs and MCCs ) of all nine studies on the remaining eight independent datasets must be assessed to achieve the comprehensive assessment of the reproducibility of the method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial improvement in the performance of new strategy was observed compared with traditional ones. The predictive performance of one study on the SZ outcome of another was reported to be a key criterion for evaluating the reproducibility of the signatures identified by different datasets . The predictive performance (both ACCs and MCCs ) of all nine studies on the remaining eight independent datasets must be assessed to achieve the comprehensive assessment of the reproducibility of the method.…”
Section: Resultsmentioning
confidence: 99%
“…The performances of one study in predicting the SZ outcome of another and vice versa were critical criteria for assessing the reproducibility of the signatures identified from independent datasets . Thus, each of the nine independent datasets (Table ) was initially selected and used to identify SZ signature.…”
Section: Methodsmentioning
confidence: 99%
“…In order to use the DEAP dataset for the experimental evaluation of the model as well as the proposed method, a further pre-process dataset was needed. First, it was necessary to define a classification methodology for the stimuli stated by subjects [41]. We preferred binary classification, as has been suggested in [32].…”
Section: Deap Datasetmentioning
confidence: 99%
“…The parameters were selected by performing informal parameter search. Random Forest was the algorithm of choice in our analysis due to its previous application to spectrotemporal features 87 and, more importantly, due to the interpretability of the resulting models. Highly interpretable structure of the resulting decision trees allowed us to follow the decision-making process that led each particular model to a decoding decision, and to estimate each feature's contribution to this process, allowing to identify and characterize category-specific spectral signatures.…”
Section: Random Forest As a Decoding Model A Random Forestmentioning
confidence: 99%